SYSTEMS AND METHODS FOR IMAGE EVALUATION (2022)
The present disclosure is related to systems and methods for image evaluation. The method may include obtaining an original image including a representation of at least one subject. The method may include generating a plurality of target positioning results for each of the at least one subject by inputting the original image into a prediction model. The prediction model may include a plurality of branches. Each of the plurality of target positioning results may correspond to a branch of the plurality of branches. The method may include determining an evaluation result corresponding to the original image based on the plurality of target positioning results.